Effect of polymer modified bitumen emulsion production method on the durability of recycled asphalt mixture in the presence of deicing agents. (8th November 2021) - Asadi Azadgoleh, Mehrdad; Modarres, Amir; Ayar, Pooyan
Graphical abstract: Highlights: SBR was added to emulsion using soap pre-batching, post-blending and co-milling methods. Sessile drop and atomic force microscopy tests were performed on modified binders. Several durability indices were performed on asphalt mix using dynamic modulus and ITS tests. Two deicing salts calcium magnesium acetate (CMA) and CaCl2 were used in durability analysis. Soap method showed the maximum adhesion and cohesive energy leading to improved durability. Abstract: This study investigated the effects of polymer modified bitumen emulsion production methods on the microstructural properties of modified binders and the mechanical properties of cold recycled mixtures with a more emphasis on durability. Modified bitumen emulsions containing styrene butadiene rubber (SBR) produced using three methods, including soap pre-batching, post-blending and co-milling. Surface free energy (SFE) and atomic force microscopy (AFM) tests have been used to inquire into the fundamental and microstructure properties of samples. Indirect tensile strength and dynamic modulus tests were used to investigate the mechanical properties of cold recycled mixtures. Mechanical properties of mixtures were investigated in dry state, after saturation and placement in the freeze-thaw (F-T) cycles with and without deicing agents including calcium magnesium acetate (CMA) and calcium chloride (CaCl2 ). Accordingly, the soap pre-batching method had the most suitable performance in terms of dynamic modulus at high temperatures and superior durability under F-T cycles. The samples made by soap pre-batching method showed the lowest surface roughness, maximum adhesion and the highest cohesive energy and surface free energy based on the results of AFM and SFE tests, which were effective in improving the mixture performance. Overall, the post-blending and co-milling methods can be rated as the second and third ranks in terms of both mechanical and nano-mechanical properties, respectively. Finally, in comparison with CaCl2, CMA salt significantly reduced the destructive effects of F-T cycles on the mechanical properties of recycled mixture.